Development of microsatellite markers for the coastal shrub Scaevola taccada (Goodeniaceae)1. (18th April 2014) - Ando, Haruko; Emura, Naoko; Denda, Tetsuro; Nakahama, Naoyuki; Inoue‐Murayama, Miho; Isagi, Yuji
Abstract : Premise of the study: Microsatellite markers were developed for the coastal shrub species Scaevola taccada to estimate the population genetic structure, which may reflect different seed dispersal patterns. Methods and Results: Thirteen microsatellite primer sets were developed for S. taccada using 454 pyrosequencing. The primer sets were tested on 64 individuals sampled from two populations in Japan. Fragments were amplified using the primers, with one to 10 alleles per locus, and the expected heterozygosity ranged from 0.00 to 0.85. Conclusions: These results indicate the utility of markers in S. taccada for broad estimations of the population genetic structure of this species.